2014
DOI: 10.2967/jnumed.114.137059
|View full text |Cite
|
Sign up to set email alerts
|

Internal Dose Assessment of (–)-18F-Flubatine, Comparing Animal Model Datasets of Mice and Piglets with First-in-Human Results

Abstract: (−)-18 F-flubatine is a promising tracer for neuroimaging of nicotinic acetylcholine receptors (nAChRs), subtype α4β2, using PET. Radiation doses after intravenous administration of the tracer in mice and piglets were assessed to determine the organ doses (ODs) and the effective dose (ED) to humans. The results were compared with subsequent clinical investigations in human volunteers. Methods: Twenty-seven female CD1 mice (weight ± SD, 28.2 ± 2.1 g) received intravenous injection of 0.75 ± 0.33 MBq of (−)-18 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Furthermore, we demonstrated the feasibility of small animal PET/MR imaging to estimate the radiation dose in humans based on mice biokinetic image data scaled to human anatomy. However, the presented study confirmed that preclinical internal dosimetry underestimates the ED in humans by 38–47 % as it has already been shown for (−)-[ 18 F]flubatine [ 16 ] and other radiotracers [ 37 40 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, we demonstrated the feasibility of small animal PET/MR imaging to estimate the radiation dose in humans based on mice biokinetic image data scaled to human anatomy. However, the presented study confirmed that preclinical internal dosimetry underestimates the ED in humans by 38–47 % as it has already been shown for (−)-[ 18 F]flubatine [ 16 ] and other radiotracers [ 37 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…The activity data of each VOI was assigned to the individual organ or tissue and subsequently transformed into percentage of injected dose (%ID organ ) with Eq. 1 [ 16 ], …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…48 The first fully automated radiosynthesis of this compound validated for human use 49 was reported in 2013 and first-in-human results of administration of the radiotracer showed no adverse effects in humans. 50 Tracer binding to plasma proteins in human blood was demonstrated in vitro and ex vivo to show no differences between patients with Alzheimer’s disease and healthy controls. 51 [ 11 C]CHIBA-1001 is a PET radiotracer for the α-7 subtype of nAChR.…”
Section: Nicotinic Acetylcholine Receptormentioning
confidence: 98%